IMPLEMENTASI METODE CONTRAST LIMITED ADAPTIVE HISTOGRAM EQUALIZATION DAN LAPLACIAN OF GAUSSIAN FILTER UNTUK PENINGKATAN KONTRAS CITRA CT - Awwalin, Aufi Rizqiatul; Setiawati, Evi; Anam, Choirul (BERKALA FISIKA, 2021)
The image obtained from the CT scanner has a relatively low contrast. Image contrast can be enhanced by using an algorithm of contrast limited adaptive histogram equalization (CLAHE). However, the implementation of CLAHE causes an increase of noise. Furthermore, noise can be reduced using a noise reduction filter, but it reduces the spatial resolution of the image. This study proposed a combination of the CLAHE method and the Laplacian of Gaussian (LoG) filter noise reduction algorithm to obtain images with high contrast, while maintaining the noise and spatial resolution. In this study, 27 abdominal CT images and MTF phantom CT images were investigated using our proposed method. As a comparison, this study also evaluated the results of combination of CLAHE and Gaussian filters. Evaluation of the results of image quality improvement was carried out qualitatively (visually) and quantitatively by calculating the mean squared error (MSE), peak-signal to noise ratio (PSNR) and spatial resolution using a modulation transfer function (MTF) of 10%. The results of this study qualitatively (visually) and quantitatively showed that the combination of CLAHE and LoG filters produces images with high contrast, while maintaining the noise and the spatial resolution of the image. Compared to the combination of CLAHE and Gaussian filters or CLAHE alone, the combination of CLAHE and Log filters provides less noise and higher spatial resolution. Thus, combination of CLAHE and LoG filters can be used as an alternative algorithm to increase the contrast in CT images.